DrugBank screening revealed alitretinoin and bexarotene as liver X receptor modulators. Issue 5 (1st March 2017) - Heitel, Pascal; Achenbach, Janosch; Moser, Daniel; Proschak, Ewgenij; Merk, Daniel
Graphical abstract: Abstract: In silico screening of DrugBank database to detect liver X receptor (LXR) agonism of marketed drugs using a self-organizing map and successive LXR-Gal4 hybrid reporter gene assay evaluation in vitro discovered alitretinoin and bexarotene as partial liver X receptor agonists. Dose-response curves demonstrated that plasma concentrations observed in clinical trials are sufficient for LXR activation and thus could account for LXR-mediated side-effects such as hypercholesterolemia and hyperlipidemia. The discovered drugs are the first reported dual LXR/RXR agonists and can serve as lead structures for LXR and dual LXR/RXR modulator development.